Fate of arsenate following arsenite oxidation in Agrobacterium tumefaciens GW4. (28th April 2014) - Wang, Qian; Qin, Dong; Zhang, Shengzhe; Wang, Lu; Li, Jingxin; Rensing, Christopher; McDermott, Timothy R.; Wang, Gejiao
Summary The fate of arsenate (AsV) generated by microbial arsenite (AsIII) oxidation is poorly understood. Agrobacterium tumefaciens wild‐type strain (GW4) was studied to determine how the cell copes with AsV generated in batch culture. GW4 grown heterotrophically with mannitol used AsIII as a supplemental energy supply as reflected by enhanced growth and increased cellular levels of NADH and ATP. Under low phosphate (Pi) conditions and presence of AsIII oxidation, up to ∼ 50% of the resulting AsV was taken up and found associated with the periplasm, membrane or cytoplasm fractions of the cells. Arsenic was found associated with proteins and polar lipids, but not in nucleic acids or sugars. Thin‐layer chromatography and gas chromatography–mass spectrometry analysis suggested the presence of arsenolipids in membranes, presumably as part of the bilayer structure of the cell membrane and replacing Pi under Pi‐limiting conditions. The potential role of a Pi‐binding protein (PstS) for AsV uptake was assessed with the His‐tag purified protein. Intrinsic tryptophan fluorescence spectra analysis suggests that PstS can bind AsV, but with lower affinity as compared with Pi. In early stationary phase cells, the AsV : Pi ratio was approximately 4.3 and accompanied by an altered cell ultrastructure.